The Critical Role of Genome Maintenance Proteins in Immune Evasion During Gammaherpesvirus Latency - Sorel, Océane; Dewals, Benjamin G. (Frontiers in Microbiology, 2019)
Gammaherpesviruses establish latent infection in their natural host for long-term persistence. During latency, the viral genome persists in the nucleus of infected cells as a circular episomal element while the viral gene expression programme is restricted to noncoding RNAs and a few number of proteins. Among these, the genome maintenance protein (GMP) is part of the small subset of transcripts highly expressed in latently infected cells. Despite sharing little peptidic sequence similarity, gammaherpesvirus-encoded GMPs contain an overall conserved structure and common functions that were shown to play essential roles in latent infection. Indeed, while GMPs are able to facilitate viral persistence in actively dividing cells through ensuring an even segregation of viral genomes in daughter cells, GMPs can also modify the cellular environment to promote cell immortalization and tumorigenesis in gammaherpesvirus-induced malignancies. In addition, one the most intriguing properties of GMPs is their capacity to evade the cytotoxic T cell response through self-limitation of MHC class I-restricted antigen presentation further ensuring virus persistence in the infected host. In this review, we give an overview of the main functions of gammaherpesvirus GMPs during latency with an emphasis on their immune evasion properties.